Neuropathic pain experience in symptomatic and presymptomatic subjects carrying a transthyretin gene mutation - Tozza, Stefano; Luigetti, Marco; Antonini, Giovanni; Mazzeo, Anna; Severi, Daniele; Di Paolantonio, Andrea; Leonardi, Luca; Russo, Massimo; Romano, Angela; Forcina, Francesca; Gentile, Luca; Nolano, Maria; et al. (Frontiers in Neurology, 2023)
Introduction Pain is a common symptom of hereditary transthyretin amyloidosis (ATTRv), however, its occurrence in late-onset ATTRv has not been investigated thoroughly. Our aim was to describe the pain experience and its impact on quality of life (QoL) in symptomatic patients and presymptomatic carriers harboring a transthyretin (TTR) gene mutation with a late-onset phenotype. Materials and methods Study participants (aged ≥18 years) were consecutively recruited from four Italian centers. Clinical disability was assessed using the Familial Amyloid Polyneuropathy (FAP) stage and Neuropathy Impairment Score (NIS). The Norfolk questionnaire evaluated QoL and the Compound Autonomic Dysfunction Test assessed autonomic involvement. Neuropathic pain was screened using the Douleur Neuropathique 4 (DN4) questionnaire, and pain intensity and its impact on daily activity were assessed using the Brief Pain Inventory severity and interference subscores. Data on the type of TTR mutation, presence of cardiomyopathy, treatment, and Body Mass Index (BMI) were collected. Results Overall, 102 subjects with TTR mutations (mean age ± SD 63.6 ± 13.5 years) were recruited, including 78 symptomatic patients (68.1 ± 10.9 years) and 24 presymptomatic carriers (49 ± 10.3 years). Pain was reported by 75.5% of all subjects, but was more frequent in symptomatic patients than in presymptomatic carriers (85.9 vs. 41.6%, respectively). Pain exhibited neuropathic features (DN4≥4) in 69.2% of symptomatic patients and in 8.3% of presymptomatic carriers. Subjects with neuropathic pain were older (p = 0.015) had worse FAP stage (p < 0.001), higher NIS scores (p < 0.001), greater autonomic involvement (p = 0.003), and a lower QoL (p < 0.001) than those without neuropathic pain. Neuropathic pain was associated with higher pain severity (p < 0.001) and had a significant negative impact on daily activities (p < 0.001) Neuropathic pain was not associated with gender, mutation type, TTR therapy, or BMI. Conclusion Approximately 70% of late-onset ATTRv patients complained of neuropathic pain (DN4≥4) that worsened as peripheral neuropathy progressed and increasingly interfered with daily activities and QoL. Notably, 8% of presymptomatic carriers complained of neuropathic pain. These results suggest that assessment of neuropathic pain may be useful to monitor disease progression and identify early manifestations of ATTRv.